The Influence of Brand Ambassador Red Velvet on Purchase Decision of BNI Tapcash - Priyambodo, Anggito; Putri, Kinkin Yuliaty Subarsa Putri; Sutjipto, Vera Wijayanti (Journal of Digital Marketing and Communication, 2025)
This research examines the influence of Red Velvet as a brand ambassador on consumer purchasing decisions for BNI’s Tapcash, an electronic payment card. Following the rise of cashless transactions post-COVID-19 and the National Cashless Movement (GNNT), BNI's collaboration with K-pop groups such as NCT 127 led to significant growth in Tapcash transactions. Building on this success, BNI launched a special edition Tapcash featuring Red Velvet to further promote its usage. The study focuses on the effectiveness of celebrity endorsements within K-pop fan culture, where fans often support idols by purchasing merchandise. Using a quantitative approach, the research surveyed the K-pop fanbase in Indonesia, specifically members of active social media communities, with 95 respondents selected through purposive sampling. The survey examined how Red Velvet’s role as a brand ambassador influenced purchasing decisions, particularly by assessing the credibility, attractiveness, and power of the brand ambassador on sales. Data analysis, conducted through validity, reliability, and simple linear regression tests, demonstrated a significant relationship between the brand ambassador and purchasing decisions. The F-value of 10.204 exceeded the F-table value of 1.989, confirming the positive effect of Red Velvet’s endorsement. Coefficient analysis indicated that a 1% increase in the Brand Ambassador variable corresponds to a 73.7% increase in purchasing decisions. This study highlights the significant role of celebrity endorsements in shaping consumer behavior, particularly within the context of the K-pop fanbase.